2022
DOI: 10.3389/fmed.2021.670229
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging-Based Phenotyping of a Singaporean Hospital-Based Cohort of High Myopia Patients

Abstract: Purpose: To assess the effect of axial length (AL) on the prevalence of pathologic myopia (PM) and associated myopic features in a Singaporean hospital-based cohort of patient with high myopia (HM).Methods: In total, 923 HM eyes from 495 individuals were recruited from the Myopic and Pathologic Eyes in Singapore (MyoPES) cohort and underwent ocular biometry, fundus photography, fundus autofluorescence, and swept-source optical coherence tomography (SS-OCT). Images were analyzed for the presence of myopic macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“… 43 , 44 In high myopes with AL exceeding 27.5 mm, the prevalence can even reach 98%. 45 The presence of β-PPA is associated with age, myopic refractive error, long AL, and visual acuity, 45 , 46 and the area of β-PPA is positively associated with AL. 47 Yan et al 32 reported that fundus tessellations were associated with β-PPA.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 In high myopes with AL exceeding 27.5 mm, the prevalence can even reach 98%. 45 The presence of β-PPA is associated with age, myopic refractive error, long AL, and visual acuity, 45 , 46 and the area of β-PPA is positively associated with AL. 47 Yan et al 32 reported that fundus tessellations were associated with β-PPA.…”
Section: Discussionmentioning
confidence: 99%
“…However, Previous research showed that adults with high myopia continue to have an increase in AL and the increased risk factors seem unchangeable [20] . Increased age, increased diopters, and AL elongation are important risk factors in fundus disease progression in patients with high myopia [21][22] . With lengthening of the AL and expansion of the eyeball, the sclera is continuously extended and thinned, leading to a series of changes in the choroid and retina and resulting in high myopia [23] .…”
Section: Discussionmentioning
confidence: 99%